Identifikasi Pengaruh Komposisi Briket Campuran (Daun Jati dan Arang Bonggol Jagung) Terhadap Karakteristik Ikan Asap - Dwi Sukowati (Journal of Natural Sciences, 2023)
The purpose of this study was to identify the effect of the composition of mixed briquettes (teak leaves and corncob charcoal) on the characteristics of smoked fish. The characteristics of the smoked fish analyzed were organoleptic. The method used in this research is experimental method. The independent variables of this study were the composition of mixed briquettes (teak leaves and corncob charcoal) with a ratio of 1:1 (Briquette A); 1:2 (Briquette B) ; 2:1 (C Briquettes). The dependent variable is the fish to be smoked. The experimental research procedure is divided into three stages, namely the preparation stage, the quality testing stage and the data analysis stage. The preparation stage includes the manufacture of fuel briquettes and the preparation of firewood and smoked fish material to be tested. The quality of smoked fish tested sensory/organoleptic includes appearance, color, aroma, taste, and texture. The results of data analysis showed that there was no significant difference in the treatment of smoked fish from the three briquettes in appearance and color, taste and texture. The significant difference is in the aroma produced by the smoked fish from the three briquettes. Fish smoked with briquette B has a more fragrant aroma than fish smoked with briquettes A and C.